Effectiveness of Vitamin D3 Supplementation and Diet Therapy on Glycemic Control and Psychological Well-being in Geriatric Patients with Type II Diabetes Mellitus at Chengalpattu Medical College—A Randomized Controlled Trial - Anitha P, Dr., Dr. Shaini G. S., Dr. Anitha Achuthan (South Eastern European Journal of Public Health, 2025)
Introduction: Type II diabetes mellitus (T2DM) is prevalent among geriatrics, causing poor glycemic control and psychological distress. This randomized controlled trial assessed the effect of vitamin D3 supplementation and diet therapy on glycemic and psychological outcomes in geriatric T2DM patients. Objectives: This study aims to assess the initial glycemic control and quality of life among senior patients with Type II Diabetes Mellitus (T2DM). It further seeks to determine the impact of Diabetic Diet therapy regimens combined with therapeutic nursing support on fasting plasma glucose (FPG), postprandial blood glucose (PPBG), and quality of life (QoL). Additionally, the study investigates the correlations between clinical outcomes and demographic factors to identify potential influences on patient health and well-being. Methods:A 12-week study involved 60 geriatric patients (≥60 years) with T2DM randomly divided into an experimental group (vitamin D3 supplementation at 1000 IU/day and a tailored diet therapy emphasizing reduced carbohydrate intake (≤50% of total caloric intake) and increased dietary fiber (≥30g/day). and a control group (placebo and standard care). Blood glucose levels (fasting glucose, postprandial glucose) and psychological well-being (assessed using the WHOQOL-BREF Psychological Domain) were evaluated. Statistical analysis utilized paired t-tests and ANCOVA. Results:The experimental group demonstrated significant reductions in mean fasting glucose (155 mg/dL to 130 mg/dL, p < 0.05), compared to the control group with no significant changes. Psychological improvements were also noted, with WHOQOL-BREF Psychological Domain scores significantly increasing from 56.8 to 68.3 (p < 0.01) in the experimental group. Conclusions: Vitamin D3 and diet therapy substantially improved glycemic control and psychological well-being in geriatric T2DM patients, emphasizing the need for holistic diabetes management approaches. Further studies are warranted to assess the long-term impact and integration into standard care.